Structural Insights into the Mechanism of Human T-cell Leukemia Virus Type 1 Gag Targeting to the Plasma Membrane for Assembly. Issue 19 (17th September 2021) - Herrmann, Dominik; Zhou, Lynne W.; Hanson, Heather M.; Willkomm, Nora A.; Mansky, Louis M.; Saad, Jamil S.
Graphical abstract: Highlights: Structure of HTLV-1 myr(-)MA share a similar globular fold to HTLV-2 myr(-)MA. HTLV-1 myr(-)MA structure revealed a membrane-interacting basic patch. HTLV-1 myr(–)MA contains a well-defined PI(4, 5)P2 binding site. Phosphatidylserine and PI(4, 5)P2 enhance myr(–) binding in a synergistic fashion. HTLV-1 Gag's myristoyl group promotes Gag puncta formation in Gag expressing cells. Abstract: Retroviral Gag targeting to the plasma membrane (PM) for assembly is mediated by the N-terminal matrix (MA) domain. For many retroviruses, Gag–PM interaction is dependent on phosphatidylinositol 4, 5-bisphosphate (PI(4, 5)P2 ). However, it has been shown that for human T-cell leukemia virus type 1 (HTLV-1), Gag binding to membranes is less dependent on PI(4, 5)P2 than HIV-1, suggesting that other factors may modulate Gag assembly. To elucidate the mechanism by which HTLV-1 Gag binds to the PM, we employed NMR techniques to determine the structure of unmyristoylated MA (myr(–)MA) and to characterize its interactions with lipids and liposomes. The MA structure consists of four α-helices and unstructured N- and C-termini. We show that myr(–)MA binds to PI(4, 5)P2 via the polar head and that binding to inositol phosphates (IPs) is significantly enhanced by increasing the number of phosphate groups on the inositol ring, indicating that the MA–IP binding is governed by charge–charge interactions. The IP binding site was mapped to a well-defined basic patch formed by lysine and arginine residues. Using an NMR-based liposome binding assay, we show that PI(4, 5)P2 and phosphatidylserine enhance myr(–)MA binding in a synergistic fashion. Confocal microscopy data revealed formation of puncta on the PM of Gag expressing cells. However, G2A-Gag mutant, lacking myristoylation, is diffuse and cytoplasmic. These results suggest that although myr(–)MA binds to membranes, myristoylation appears to be key for formation of HTLV-1 Gag puncta on the PM. Altogether, these findings advance our understanding of a key mechanism in retroviral assembly.